Association between specific social activities and depressive symptoms among older adults: A study of urban-rural differences in China - Han, Tanqian; Han, Mei; Moreira, Paulo; Song, Hongxia; Li, Ping; Zhang, Zhenlong (Frontiers in Public Health, 2023)
Background Engaging in social activities can help older persons with their depressed symptoms. Few studies, however, have looked into the connection between social interactions and depressed symptoms in Chinese older persons. The aim of this study was to investigate differences in older Chinese individuals' social activity involvement and depressive symptoms across urban and rural settings. Methods A cross-sectional investigation using information from the 2018 China Health and Retirement Longitudinal Study (CHARLS), which was limited to older individuals aged 60 and over. Generalized linear models were constructed to assess the effects of participants' characteristics and specific social activities on CES-D scores. The association between specific social activities and depressed symptoms was investigated using multivariate logistic regression analysis. Results In this study, it was discovered that older individuals had a prevalence of depressed symptoms of 36.2%, with rural older adults having a greater prevalence of depressive symptoms (39.7%) than urban older adults (30.9%). Our results showed that for urban respondents, providing help to others (not regularly. OR = 0.753, 95% CI: 0.579–0.980, P = 0.035), going to a sport (not regularly. OR = 0.685, 95% CI: 0.508–0.924, P = 0.013), and using the Internet (not regular. OR = 0.613, 95% CI: 0.477–0.789, P < 0.001; almost weekly. OR = 0.196, 95% CI: 0.060–0.645, P = 0.007) were all significantly and negatively associated with depressive symptoms, while for rural respondents, interacting with friends (not regularly. OR = 1.205, 95% CI: 1.028–01.412, P = 0.021) and using the Internet (not regularly. OR = 0.441, 95% CI: 0.278–0.698, P < 0.001) were significantly and negatively associated with depressive symptoms. Conclusions According to our research, there is a cross-sectional relationship between participating in a specific social activity and depressed symptoms in Chinese older adults, and this relationship varies across urban and rural older adults. This suggests that taking part in specific social activities may be crucial for reducing depression symptoms in older persons, developing more focused interventions that might support healthy aging, and offering a guide for policymakers and activists working to improve the mental health of seniors.